5th IEEE Conference on Nanotechnology, 2005.
DOI: 10.1109/nano.2005.1500853
|View full text |Cite
|
Sign up to set email alerts
|

Catalyst free low temperature direct growth of carbon nanotubes

Abstract: A metal catalyst free direct growth process has been developed for the CVD of carbon nanotubes (CNTs) on carbon implanted SiGe islands or Ge dots on Si substrates. From TEM and Raman measurements, the fabricated CNTs are identified as single-walled CNTs (SWNTs) with diameter ranging from 1.2 to 2.1 nm. Essential parts of the substrate preparation after SiGe or Ge dot growth and carbon ion implantation are a chemical oxidation and preheating at 1000 °C prior to CNT growth. We believe that the lower melting poin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…The potential of semiconducting catalyst particles was first demonstrated by Uchino et al [ 29 , 30 ] in which carbon-doped SiGe islands on Si were used to grow CNT after chemical oxidation and annealing treatments. Growth of the CNT was argued to occur from Ge clusters.…”
Section: Ceramic and Semiconductor Catalystsmentioning
confidence: 99%
“…The potential of semiconducting catalyst particles was first demonstrated by Uchino et al [ 29 , 30 ] in which carbon-doped SiGe islands on Si were used to grow CNT after chemical oxidation and annealing treatments. Growth of the CNT was argued to occur from Ge clusters.…”
Section: Ceramic and Semiconductor Catalystsmentioning
confidence: 99%
“…10) In our previous work on the growth of CNTs on Si using Ge nanostructures, we found that the growth of CNTs was possible from Ge nanoparticles without the presence of a metal catalyst. [11][12][13] However, in this work, the results in Fig. 4 indicate that CNTs were grown from the Fe nanoparticles, rather than the Ge nanoparticles.…”
Section: Resultsmentioning
confidence: 58%
“…The SiGe islands have heights ranging from 20 to 50 nm 13) and the Ge dots have diameters ranging from 20 to 250 nm and heights ranging from 10 to 25 nm. 14) Then the wafers were implanted with carbon at a dose of 3×10 16 cm -2 and an energy of 30 keV. The wafers were cut into 5×7 mm pieces and dipped in buffered hydrofluoric acid (HF) solution to remove the native oxide.…”
Section: Methodsmentioning
confidence: 99%